Laparoskopische vs. offene Rektumresektion: onkologisch gleichwertig? = Laparoscopic versus open rectal cancer resection : oncologically equal? - Müller, Beat P.; Wagner, Martin; Steinemann, Daniel (Der Chirurg, 2016)
The oncological equivalence of laparoscopic and open rectal cancer resection was evaluated in four multicenter randomized controlled trials. The COLOR II and the COREAN trials demonstrated oncological equivalence; however, the ACOSOG and the ALaCaRT studies came to a different conclusion. In the latter two studies a composite endpoint that assessed the quality of the mesorectal specimen, the completeness of tumor-free circumferential and distal resection margins was chosen. In both trials a higher success rate for open surgery was shown; nevertheless, the validity of this composite endpoint has not been proven and no conclusions on solid oncological endpoints can be drawn. The COLOR II and the COREAN trial therefore remain the only available studies which investigated solid oncological endpoints, such as local recurrence and disease-free survival over an adequate follow-up time period of 3 years; however, the comparability of the study groups at least of the COLOR II trial needs to be called into question as only the experience of the laparoscopic surgeons was assessed. With a local recurrence rate of 5 % in both groups the oncological quality seems nevertheless to be good; therefore, a systematically inadequate control group should not be assumed. At this point it can be concluded that a good oncological outcome can be achieved with laparoscopic rectal resection in the hands of experts. For a final assessment the long-term results of the on-going trials needs to be awaited. If the promising results for laparoscopic surgery of the COLOR II trial are confirmed laparoscopic rectal resection should be preferred to open resection in the future. This conclusion is based on the generally known perioperative benefits of minimally invasive surgery.